1999
DOI: 10.21273/jashs.124.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Continuous and Discrete Plant and Soil Water Status Monitoring in Peach Trees Subjected to Deficit Irrigation

Abstract: To characterize tree responses to water deficits in shallow and deep rooted conditions, parameters developed using daily oscillations from continuously measured soil water content and trunk diameter were compared with traditional discrete monitoring of soil and plant water status in lysimeter and field-grown peach trees [Prunus persica (L.) Batsch `O'Henry']. Evaluation occurred during the imposition of deficit irrigation for 21 days followed by full irrigation for 17 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(68 citation statements)
references
References 27 publications
(28 reference statements)
6
45
0
17
Order By: Relevance
“…It should be noted that the measurement of leaf water potential in non-transpiring leaves (stem water potential) will almost certainly produce a more intense signal than that observed in sun-exposed transpiring leaves (Goldhamer et al 1999, Ortuño et al 2006). More research is needed before we can confirm what is the best plant water stress indicator for adult apricot trees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the measurement of leaf water potential in non-transpiring leaves (stem water potential) will almost certainly produce a more intense signal than that observed in sun-exposed transpiring leaves (Goldhamer et al 1999, Ortuño et al 2006). More research is needed before we can confirm what is the best plant water stress indicator for adult apricot trees.…”
Section: Resultsmentioning
confidence: 99%
“…Gas exchange parameters, such as variations in stomatal conductance, have also been used as water status indicators (Harrison et al 1989). More recently, some sensors used to measure sap flow and trunk diameter fluctuation have provided useful information about water status because of the continuous nature of the measurements; they have also proved to be very robust (Goldhamer et al 1999, Remorini and Massai 2003, Ohashi et al 2006, Ortuño et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Pataki and Oren (2003) studied factors controlling transpiration of some trees species, and showed that Quercus rubra, Q. alba, Carya tormentosa and Fraxinus americana plants were responsive to vapour pressure deficit and presented saturation in increases in daily sap flux density with vapour pressure deficit, these responses being similar at different soil moisture levels. Moreover, considering that MDS respond sooner to water stress than other continuous and discrete plant and soil water status indicators (Goldhamer et al, 1999) and that MDS is a versatile indicator of transpiration stream intensity when the soil water content is not strongly depleted (Huguet et al, 1992;Ortun˜o et al, 2004a, b), the fact that when SF presented high and constant values (Figure 2c) MDS values progressively decreased (Figure 2b) indicated that lemon trees were not under a water stress situation.…”
Section: Discussionmentioning
confidence: 97%
“…These techniques permit continuous and automated registers of the plant water status, and an immediate, consistent and reliable response to water deficit (Goldhamer et al, 1999;Ortun˜o et al, 2004a, b), with a reduction in the labour needed for the measurement procedure. Goldhamer and Fereres (2004) obtained promising results using only maximum daily trunk shrinkage (MDS) for scheduling almond trees irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Goldhamer et al (1999) indicated that MDS responded sooner than stem to water stress, and Ortuño et al (2004b) showed that in young lemon trees continuously measured plant water status indicators were more immediate and sensitive than discretely measured indicators.…”
Section: Discussionmentioning
confidence: 99%